Implementasi Kebijakan Peraturan Daerah No. 03 Tahun 2016 Tentang Kawasan Tanpa Rokok di Dinas Kesehatan Kabupaten Paser - Kurniawan, Ahmad; Idris, Adam; Dyastari, Letizia (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Implementation of Regional Regulation Policy No.03 of 2016 concerning Non- Smoking Areas in the Paser District Health Service (supervised by Prof. Dr. H. Adam Idris, M. Si as supervisor I and Mohammad Taufik, S. Sos, M. Si as lecturer supervisor II). The aim of this research is to determine the implementation of Regional Regulation Policy No.03 of 2016 concerning No-Smoking Areas in the Paser District Health Service. Search data obtained from interviews and observations. Meanwhile, The research methodology used is qualitative, specifically using the phenomenological approach. Primary and secondary data are the two main types of research data sources. There were a total of six research informants. The used analytical method involves data manipulation, data representation, and the derivation of findings, followed by their validation. The research results show that the implementation of regional regulation policy no. 3 of 2016 concerning No- Smoking Areas in the Paser District Health Service uses the Soren implementation model. C. Winter, is already running even though implementation is not yet optimal. Therefore, Efforts such as socialisation and counselling by government agencies, including the Paser District Health Service, in collaboration with other relevant institutions, are imperative. However, the implementation of the Regional Regulation on No-Smoking Areas has proven to be unsuccessful.